Uganda : An NGO Perspective to Countering Violent Extremism - Ekayu, Jane; S. Rajaratnam School of International Studies (S. Rajaratnam School of International Studies (RSIS), 2015)
After two decades of civil war, Northern Uganda is home to thousands of former child soldiers in search for their place in the world. Peacekeeping organisations in the region are assisting these former child soldiers and their communities to rebuild their lives. One such organisation is the Children of Peace Uganda, a non-governmental organisation (NGO) working to minimise the risk of violent extremism in the society through peacebuilding efforts.
Keywords: Terrorismo -- Movimientos extremistas; Conflictos armados; Paz; Prospectiva; Uganda